دراسة الأخطاء الاملائية لدى المعاق سمعيا دراسة ميدانية مدرسة الأطفال المعاقيين سمعيا بمدينة الأغواط - شيماء عطلي; سعاد ابراهيمي (My University, 2023)
The current study intends to investigate the spelling errors of the hearing challenged. And the descriptive approach was utilized to accomplish this pupose. Boumaraf et al. (2023) used the written word completion test, which is part of the scholastic aptitude test adapted to the Arabic language. The findings revealed that children with hearing impairments, the study sample, suffer from spelling errors, and that there are differences in test results related to visual and auditory inputs based on academic level and severity of hearing impairment. Keywords: misspellings, hearing disability – auditory entance. Visual input.